Pengaruh Daya Tarik Webtoon “The Secret of Angel” Terhadap Minat Baca Di Komunitas Penggemar Webtoon - Uswatun Khasanah; Labibah Labibah (Pustakaloka, 2021)
Abstract: This study aims to: (1) describe the perception of the webtoon fans community on the attractiveness of the secret of angel webtoon; (2) describe reading interest in the webtoon fans community; (3) describe the effect of the secret of angel's webtoon attractiveness on reading interest in the webtoon fans community. This research includes quantitative research with descriptive research methods. The research subject is the webtoon fans community and the object is the attraction of the secret of angel webtoon. The variables in the study were the variable webtoon attractiveness and reading interest. The population in this study is the webtoon fan community on Telegram called Fans Webtoon Indonesia. The results stated that the perception of the webtoon fan community towards the attractiveness of the secret of angel webtoon is in the very good category and the reading interest of webtoon fans community is in the good category. For the results of the simple linear regression test, it can be seen that the attractiveness of the secret of angel webtoon affects the reading interest of the webtoon fan community by 38,2%.